МЕЙНСТРИМ РОЗВИТКУ ПІДПРИЄМСТВ ЕЛЕКТРОЕНЕРГЕТИЧНОЇ ГАЛУЗІ - Валінкевич, Наталія Василівна; Безсмертний, Сергій Олександрович (TIME DESCRIPTION OF ECONOMIC REFORMS, 2025)
The mainstream of development of enterprises in the electric power industry is decentralization, the development of renewable energy sources, the active role of consumers, innovations and ensuring the country's energy independence, which are constantly changing and require constant monitoring and analysis.  The article is aimed at highlighting the results of the study of the mainstream development of enterprises in the electric power industry. Methods used in the study: chorological, classification, detailing and generalization, grouping, complex, tabular, etc. The hypothesis of the study was the assumption that the mainstream development of enterprises in the electric power industry is transformed due to changes in history, leaders, determinants and tools. Presentation of the main material. Based on the results of scientific research of the mainstream development of enterprises in the electric power industry, the key economic aspects of their functioning have been identified, the history of the development of the electric power industry has been analyzed, and energy efficiency as one of the determining determinants of the energy complex and the Energy Strategy of Ukraine until 2050 has been outlined. The essence of the concepts of "energy saving" and "energy efficiency" has been clarified and leaders of the energy complex of Ukraine in 2023, which made it possible to form a rating of the most successful companies in the energy sector, which included five leading enterprises owned by the state, but only two managed to increase their income. In terms of management and ownership, the Ukrainian energy system consists of main power lines and generation capacities. The article classifies the types of economic activity according to the Classification of Economic Activities, which covers the supply of electricity, natural gas, steam, hot water and other energy resources through permanent infrastructure — power lines, cable networks, gas pipelines and water pipelines. Ukraine continues to actively implement the Classification of Economic Activities aimed at unifying the classification of industries, which contributes to better interaction between different sectors of the economy and business entities. The originality and practical significance of the study lies in determining the modern aspects of the mainstream development of enterprises in the electric power industry. Conclusions. The mainstream of development of enterprises in the electric power industry depends on market leaders, determinants and tools for the functioning of electric power enterprises. Further research consists  in continuing the study of the spatial organization of electric power enterprises, developing mechanisms for adaptation to wartime conditions and post-war recovery, as well as intensifying integration with European energy markets